A Validation Study of the Mini-IPIP Five-Factor Personality Scale in Adults with Cancer - Perry, Laura M. (J Pers Assess, 2019)
The mini-IPIP is a brief measure of the Five-Factor model of personality with documented validity in healthy samples of adults and may be useful for assessing personality in patient populations such as individuals with cancer. The purpose of the present study was to examine the psychometric properties of the mini-IPIP in two samples of adults with cancer. A sample of 369 (Sample 1) and a sample of 459 (Sample 2) adults with cancer completed an online survey including the mini-IPIP. To assess criterion validity, Sample 2 completed measures of emotional distress. Analyses included internal consistency (Samples 1 and 2), CFAs (Samples 1 and 2), and correlations and a structural regression model to examine the associations between the five personality factors and emotional distress (Sample 2 only). Results showed that the mini-IPIP demonstrated levels of internal consistency and CFA model fit that were similar to previous validation studies conducted in the general population. Consistent with prior research and theory, this study also found that personality factors measured by the mini-IPIP were associated with measures of emotional distress in Sample 2. These findings suggest the potential utility of the mini-IPIP in both research and clinical settings involving individuals with cancer.